Environment and natural resource conservation and management in Mozambique - Mawere, Munyaradzi ([Oxford] : Langaa Research & Publishing CIG, 2013)
This is a narrative of the environmental and natural resource conservation and management issues in Mozambique. While the topics in this volume are diverse, they are all explicitly designed to move beyond the routinized blame of natural resource mismanagement and environmental degradation on local communities, and to rethink ecosystem destruction, land degradation, and natural resource over-exploitation in Africa and beyond. Never losing sight of the major causes of environment and resource mismanagement in Mozambique, the book advances the thesis that environment and resource problems are a result of compound factors such as poor governance, poverty, corruption, low education levels, and disregard of endogenous conservation epistemologies. A combination of all these factors makes the terrain of conservation even more complicated than ever; hence the need for urgent action by all social actors.
Situating Mozambique's Natural Resource Management in Historical Context -- Environmental Malpractices in Mozambique : A Case Study of Xai-Xai Rural Area, Gaza Province, Mozambique -- Green Revolution Program (GRP) in Mozambique : Rethinking the Impact of Mozambique's Fast-Track GRP on the Environment and Biodiversity -- Gold Panning in Central Mozambique : A Critical Investigation of the Effects of Gold Panning in Manica Province -- Community-Based Natural Resource Management (CBNRM) in Mozambique : Lessons and Directions for Natural Resource Management -- "It's Neither Conservation nor Preservation" : Possibilities for Alleviating Poverty through Dambo Utilization in Chokwe Rural Area, Gaza Province, Mozambique -- Small-Scale Cash Income Sources in Central Mozambique : The Root Cause of Resource Scarcity and Environmental Instability? -- Unlocking the Crisis : New Directions for Conservation in Mozambique.
Print version record.
eBooks on EBSCOhost
Keywords: Nature conservation -- Government policy -- Mozambique; Conservation of natural resources -- Mozambique; Mozambique -- Environmental conditions; Nature -- Conservation -- Politique gouvernementale -- Mozambique; Conservation des ressources naturelles -- Mozambique; BUSINESS & ECONOMICS -- Development -- Sustainable Development; NATURE -- Environmental Conservation & Protection; Conservation of natural resources; Ecology; Nature conservation -- Government policy; Mozambique